USP4 interacts and positively regulates IRF8 function via K48‐linked deubiquitination in regulatory T cells. Issue 12 (7th June 2017) - Lin, Ruirong; Nie, Jia; Ren, Jiazi; Liang, Rui; Li, Dan; Wang, Ping; Gao, Chengjiang; Zhuo, Changhua; Yang, Chunkang; Li, Bin
Abstract : CD4 + CD25 + regulatory T (Treg) cells comprise a unique subset of T cells required for maintaining immune homeostasis. However, the molecular mechanisms associated with the functional variety of Treg cells are not fully delineated. In the present study, we demonstrate that ubiquitin‐specific protease (USP)4 physically interacted with interferon regulatory factor 8 (IRF8) function via a K48‐linked deubiquitinase, which stabilized IRF8 protein levels in Treg cells. Depletion of USP4 promoted the polyubiquitination of IRF8 and the upregulation of type 2 inflammatory cytokine gene expression in Treg cells. Consistently, treatment of Treg cells with USP4 inhibitor facilitated the polyubiquitination of IRF8. In addition, the deficiency of USP4 alleviated the suppressive function of Treg cells. Taken together, our results suggest that USP4 interacts with and stabilizes IRF8 to promote the suppressive function of Treg cells. Abstract :